STRIPAK regulation of katanin microtubule severing in the Caenorhabditis elegans embryo. Issue 1 (17th March 2022) - Lu, Tammy; Smit, Ryan B; Soueid, Hanifa; Mains, Paul E
Abstract: Microtubule severing plays important role in cell structure and cell division. The microtubule severing protein katanin, composed of the MEI-1/MEI-2 subunits in Caenorhabditis elegans, is required for oocyte meiotic spindle formation; however, it must be inactivated for mitosis to proceed as continued katanin expression is lethal. Katanin activity is regulated by 2 ubiquitin-based protein degradation pathways. Another ubiquitin ligase, HECD-1, the homolog of human HECTD1/HECT domain E3 ubiquitin protein ligase 1, regulates katanin activity without affecting katanin levels. In other organisms, HECD-1 is a component of the striatin-interacting kinase phosphatase complex, which affects cell proliferation and a variety of signaling pathways. Here we conducted a systematic screen of how mutations in striatin-interacting kinase phosphatase components affect katanin function in C. elegans . Striatin-interacting kinase phosphatase core components (FARL-11, CASH-1, LET-92, and GCK-1) were katanin inhibitors in mitosis and activators in meiosis, much like HECD-1. By contrast, variable components (SLMP-1, OTUB-2) functioned as activators of katanin activity in mitosis, indicating they may function to alter striatin-interacting kinase phosphatase core function. The core component CCM-3 acted as an inhibitor at both divisions, while other components (MOB-4, C49H3.6) showed weak interactions with katanin mutants. Additional experiments indicate that katanin may be involved with the centralspindlin complex and a tubulin chaperone. HECD-1 shows ubiquitous expression in the cytoplasm throughout meiosis and early development. The differing functions of the different subunits could contribute to the diverse functions of the striatin-interacting kinase phosphatase complex in C. elegans and other organisms.